Synthesis and Structural Characterization of Branched Bimetallic AuPd Nanoparticles with a Highly Tunable Optical Response - Nuti, Silvia (2023)
Funding Information: The authors thank the financial support by the PROTEOMASS Scientific Society (Portugal) (General Funding Grant 2023). The authors acknowledge funding from the European Union’s Horizon 2020 Research and Innovation Program under Grant 823717-ESTEEM3, and Ana B. Hungría thanks the financial support from Junta de Andalucía Project P20_00968. Javier Fernández-Lodeiro thanks FCT for the research contract through the Program DL 57/2016-Norma Transitória. The work was carried out partially through the INL User Facilities (Braga, Portugal) and the Electron Microscope Division (DME) of the Servicios Centrales de Investigación Científica y Tecnológica (SC-ICYT) at Cadiz University (Cadiz, Spain). The authors thank Dr. Jamila Djafari for the assistance with the design of the graphical abstract. Funding Information: This work received financial support from Portugal national funds [Fundação para a Ciência e Tecnologia and Ministério da Ciência, Tecnologia e Ensino Superior (FCT/MCTES)] through the Projects UIDB/50006/2020 and UIDP/50006/2020. Silvia Nuti, Carlos Lodeiro, José-Luis Capelo-Martinez, Adrián Fernández-Lodeiro, and Javier Fernández-Lodeiro thank the financial support from national funds (FCT/MCTES) through Project Met4Cat (EXPL/QUI-COL/0263/2021). The authors thank the financial support by the PROTEOMASS Scientific Society (Portugal) (General Funding Grant 2023). The authors acknowledge funding from the European Union’s Horizon 2020 Research and Innovation Program under Grant 823717-ESTEEM3, and Ana B. Hungría thanks the financial support from Junta de Andalucía Project P20_00968. Silvia Nuti thanks FCT/MCTEC (Portugal) for her doctoral grant associated with the chemistry Ph.D. program (SFRH/BD/144618/2019). Javier Fernández-Lodeiro thanks FCT for the research contract through the Program DL 57/2016–Norma Transitória. The work was carried out partially through the INL User Facilities (Braga, Portugal) and the Electron Microscope Division (DME) of the Servicios Centrales de Investigación Científica y Tecnológica (SC-ICYT) at Cadiz University (Cadiz, Spain). The authors thank Dr. Jamila Djafari for the assistance with the design of the graphical abstract. Publisher Copyright: © 2023 The Authors. Published by American Chemical Society.